2015
DOI: 10.1007/s13595-015-0533-2
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground biomass equations for sustainable production of fuelwood in a native dry tropical afro-montane forest of Ethiopia

Abstract: Abstract& Key message Biomass equations are presented for five tree species growing in a natural forest in Ethiopia. Fitted models showed more accurate estimations than published generalized models for this dry tropical forest. & Context Biomass equations are needed to correctly quantify harvestable stock and biomass for sustainability efforts in forest management, but this kind of information is scarce in Ethiopia. & Aims This study sought to develop biomass models for five of the most common native tree spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 47 publications
(66 reference statements)
4
31
2
1
Order By: Relevance
“…It is not surprising that the best local multispecies model from this study performed better than the previously published general models (Table 6). Such a result also emphasizes the importance to develop local models to get more accurate biomass estimations when local estimates are required [9,18]. The two pan-tropical general multispecies models developed for dry tropical forests [10] and for all tropical forests [11] gave relatively good predictions with nonsignificant differences for our site (5.2% and 5.3% respectively).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It is not surprising that the best local multispecies model from this study performed better than the previously published general models (Table 6). Such a result also emphasizes the importance to develop local models to get more accurate biomass estimations when local estimates are required [9,18]. The two pan-tropical general multispecies models developed for dry tropical forests [10] and for all tropical forests [11] gave relatively good predictions with nonsignificant differences for our site (5.2% and 5.3% respectively).…”
Section: Discussionmentioning
confidence: 63%
“…For instance, the general multispecies pan-tropical models developed by Chave et al [10,11] have been used for estimating AGB of different forest types in many parts of the world, including Ethiopia. Nevertheless, there are many studies (e.g., [15,18,19]) that showed a significant bias in AGB for different forest types when these models were applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La variación explicada por las ecuaciones de aditividad fue alta, esto se debe a que en su estructura se incluyeron como variables independientes al Dn y a la H. El uso de estas variables en la predicción de la biomasa ha sido discutido ampliamente por diferentes autores, debido a que pueden mejorar significativamente los resultados de ajuste y la capacidad de predicción (Bi et al, 2004;Li y Zhao, 2013), en lugar de emplear únicamente al Dn como variable predictora. Además, al incluir a la H en las ecuaciones se tiene información relacionada sobre la competencia y/o fertilidad del sitio ocasionando estimaciones menos sesgadas (Tesfaye et al, 2015). El uso del Dn como única variable predictora para la estimación de biomasa a nivel del árbol, ha mostrado buenos estadísticos de ajuste para diferentes especies de coníferas (Návar, González, Graciano, Dale y Parresol, 2004;Acosta-Mireles et al;2002;Díaz-Franco et al, 2007).…”
Section: Discussionunclassified
“…This is due the fact that the country has a wide variety of ecological characteristics associated with ample diversity of plant and animal species (Alemayehu, 2002). However, a number of studies indicated that almost all of the natural vegetation of Ethiopia is under an extreme pressure of anthropogenic threats (Yirdaw, 1996;Million, 2001;Tesfaye, 2015;Newton and Cantarello 2015). Given about 85% of the population Ethiopia is living in the rural areas, their livelihood system is either directly or indirectly depends on agriculture, which provides about 52% of the country's GDP (World Bank, 2000;CIA, 2001).…”
Section: Introductionmentioning
confidence: 99%